A review of the genus Xiphovelia Lundblad, 1933 (Hemiptera: Heteroptera: Veliidae) from China, with descriptions of three new species - Ye, Zhen; Bu, Wenjun (Zootaxa, 2015)
Four species of genus Xiphovelia Lundblad are now known from China. Of these, X. glauca Esaki & Miyamoto, 1959 is the only member of the genus previously recorded from China. In addition, three species, X. denigrata sp. nov., X. fulva sp. nov. and X. reflexa sp. nov., are described as new to science. Photographs of the male and female dorsal habitus, male fore and middle legs, male abdominal segment VIII and endosoma with pygophore are provided, accompanied by habitat photographs and a distribution map for all Chinese Xiphovelia species. A key to all the four Chinese Xiphovelia species is also provided.